Legislatures of small states : a comparative study - Baldwin, Nicholas (Library of legislative studies., 2013)
"This book provides a comparative study of the legislatures of small nations, states and territories, to explore the extent to which size is a factor in how they function and fulfil the roles and responsibility of a legislature.Though the physical nature and environment of states is a neglected subject in political science research, this book examines the impact of small state size on the structure and functions of legislatures and contributes to a better understanding of the interplay of physical and social factors. Focussing on legislatures in democratic nations or in territories that are parts of democratic units, the book features case studies on Malta, Bermuda, Jersey, Guernsey, Gibraltar, Hong Kong, Lesotho, Liechtenstein, the Isle of Man, Commonwealth Caribbean, Nunavut (Canada), Pacific islands, Swaziland, and Scotland. Contributors employ an interdisciplinary approach to examine both the outcomes and causes of different political mechanisms, and bring to the surface underlying correlation between small states through their analysis. Legislatures of Small States will be of interest to students and scholars of international politics, comparative politics and legislative studies"--